EVALUATION OF TRAMSET CONFIGURATION BASED ON PERFORMANCE IN CURVE TRACK - Ramadoni, Ahmad
Tram is one of light rail train that operated in the city and has a rail that is on the same level as the city road. As result, trem could reach the downtown, atractive spot, shoping center, and tourist destination. Hence, Tram must be able to go through a very small curve up to radius of 25 meters. Such this operation conditions, trem need a special carbody and bogie configurations, unlike a common train. Currently, indonesian rolling stock manufacturer company is developing a low floor vehicle or tram and reviewing the trem configurations which is exactly match with operating conditions in Indonesia. Trem bogie and carbody configuration will determine the ability to pass a curve. There are three types tram configurations, namely single articulation, multi articulation, and Jakob's type bogie. It is necessary to do an analysis based on operating conditions to choose the right configuration. Analysis of the tram configuration was initially carried out based on the graphical analysis using Autodesk Inventor Software then an analysis of lateral force using Heumann method. Based on the graphical analysis and lateral force analysis using Heumann method, a single articulation configuration was finally chosen as a tram configuration. A single articulated configuration tram is then modeled and simulated in Universal Mechanism Software to evaluate the performance in the smallest operational curve based on GM/RT 2141 and EN 14363 standards. Based on the simulation results, all “safety against derailment” parameters obtained are still below the maximum allowable value on GM/RT 2141 and EN 14363 standards. This shows that the tram is declared safe when operated in the smallest operational curvature.